2018
DOI: 10.1093/jas/skx033
|View full text |Cite
|
Sign up to set email alerts
|

Serum and plasma metabolites associated with postpartum ovulation and pregnancy risks in suckled beef cows subjected to artificial insemination1

Abstract: Two experiments were conducted to determine relationships of blood metabolite concentrations, BW, BCS, and rump fat depth with postpartum ovulation and pregnancy risks, as well as their utility in predicting those outcomes in suckled beef cows. In experiment 1, plasma glucose collected 10 and 3 d before AI of suckled beef cows at seven locations did not differ between cows that had resumed estrous cycles (ovulated) before AI compared with anovulatory cows, whereas plasma glucose 3 d before AI was greater (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…In this study, the subcutaneous back fat tended to be higher in all the cyclic animals as compared to cystic and acyclic yaks. These findings are supported by earlier studies that the back‐fat values decrease considerably after calving for animals that are not pregnant and non‐cycling (Diaz et al., 2018; Hill et al., 2018). It is well established that cows overconditioned at calving will exhibit decreased appetite (lower dietary intake) and develop more severe NEB than the cows in the moderate condition (Garnsworthy & Topps, 1982; Treacher et al., 1986).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the subcutaneous back fat tended to be higher in all the cyclic animals as compared to cystic and acyclic yaks. These findings are supported by earlier studies that the back‐fat values decrease considerably after calving for animals that are not pregnant and non‐cycling (Diaz et al., 2018; Hill et al., 2018). It is well established that cows overconditioned at calving will exhibit decreased appetite (lower dietary intake) and develop more severe NEB than the cows in the moderate condition (Garnsworthy & Topps, 1982; Treacher et al., 1986).…”
Section: Discussionsupporting
confidence: 85%
“…Cows that maintained BCS during the postpartum period had a shorter interval to estrus, greater levels of basal LH and enhanced response to GnRH induced LH release [48].A study including 3,269 cows in seven different studies reported a linear increase of 18 % in the number of cyclic cows for each unit of BCS increase from ≤ 3.5 to ≥ 6.0 of a 1 (thin) to 9 (fat) scale [45].Rump fat and BCS were greater and serum concentration of BHB and NEFA reduced during the six weeks after parturition in cows that ovulated before first AI and become pregnant [49].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin treatment has successfully been used to initiate ovarian cyclicity in anoestrous buffalo heifers 11 and increase plasma concentrations of GnRH and gonadotropins, promoting follicular growth and ovulation 12, 13 . The conception rate following AI is usually between 30% and 70% 14–22 . Early embryonic development may be negatively affected by insufficient progesterone (P4) production, with pregnancy failure attributed to insufficient luteal P4 production during early embryonic development 23 …”
mentioning
confidence: 99%